The Role of Electronic Human Resource Management (E-HRM) and Career Planning on the Performance of Bank Employees in South Tangerang - Hamsinah Hamsinah (Universitas Dharma Wacana, 2022)
The success of an organization cannot be separated from the improvement of human resources. This study aims to analyze the effect of the electronic human resource management (E-HRM) variable on the Bank's Employee Performance, analyze the Bank's career planning process on the Bank's employee performance. The research was conducted using a quantitative approach through a survey. The population of this study were all employees, while the number of samples in this study were 300 people using simple random sampling. Testing the hypothesis in this study using SEM (Structural Equation Modeling) with the PLS program. The research data was obtained through the distribution of online questionnaires. The results of this study indicate that there is a direct influence between electronic human resource management (E-HRM) on the performance of bank employees, there is a direct influence between career planning on employee performance. Based on the research results, it is hoped that all bank management will make clear career plans for their employees so that they are more enthusiastic in working and will lead to job satisfaction which will ultimately improve their performance and implement Electronic Human Resource Management (E-HRM) to improve employee performance.Â